PERSEPSI POLITIK ORGANISASI DALAM RUANG KERJA PNS: PERSPEKTIF ACEH BARAT - Rusdi Rusdi; Muhammad Rahmat Hidayat (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to understand how perceived organizational politics affects the interactions among Civil Servants (Pegawai Negeri Sipil - PNS) in West Aceh. 472 respondents were collected for the study and analyzed using the partial least square method. The research findings revealed that relationship and communication do not directly influence meaningful work. However, in the context of perceived organizational politics (POP), meaningful work plays a crucial role in reducing the negative effects of organizational politics. Employees who perceive their work as meaningful show higher motivation, reduced tension, increased engagement, and greater commitment to the organization. A positive organizational reputation and meaningful work together contribute to reducing perceived organizational politics, creating a harmonious and productive work environment. While resource does not affect meaningful work, unfair resource competition can impact employee engagement by causing dissatisfaction and reduced collaboration. Therefore, PNS management needs to create a fair, transparent, and empowering work environment to enhance employee engagement and well-being. These research findings offer valuable insights for organizational managers in understanding the importance of fostering a meaningful work environment and reducing disruptive organizational politics for employees.